4D printing technology : principles, materials and applications - Bikram Samal, Bijaya; Siva Kumar, Cheruvu; Kumar Varshney, Shailendra (Advances in Additive Manufacturing Technologies, 2025)
The book serves as a comprehensive guide to 4D printing technology, exploring its principles, materials, and applications while offering valuable insights for researchers, engineers, and innovators in additive manufacturing.4D Printing Technology: Principles, Materials and Applications is a detailed exploration of 4D printing technology, offering readers a comprehensive understanding of how smart materials and additive manufacturing processes come together to create dynamic, responsive structures. Starting with the foundations of additive manufacturing, this volume introduces readers to the rise of smart materials and the evolution from static 3D printing to adaptive 4D printing. It covers a wide range of topics, including 4D printing at the micro and nano scale, the use of polymers and reinforced materials, and advanced applications in photonics. The volume delves into complex programming of 4D printed materials, discussing various stimuli (thermal, magnetic, light-based) that enable shape-shifting behavior. Each chapter focuses on practical applications, including healthcare innovations like adaptive implants, aerospace components that morph based on environmental conditions, and novel photonic devices. Finally, the book discusses key characterization techniques necessary for analyzing the performance and durability of 4D printed parts. 4D Printing Technology: Principles, Materials and Applications serves as a comprehensive reference and an inspiration for future innovations in this rapidly evolving field.Readers will find the book - Comprehensively covers 4D printing technologies, from foundational principles to advanced applications in photonics, robotics, and micro/nano devices;- Includes contributions from international experts in smart materials, advanced manufacturing techniques, and application-specific innovations;- Covers important research developments in this field from the last decade;- Provides detailed discussions on materials, shape programming, and characterization techniques for 4D printed structures;- Examines various applications, future directions, and innovations in 4D printing, smart materials, and additive manufacturing technologies